Epidemiological Survey of Urinary Incontinence and Its Impact on Quality of Life in Women Aged 40-60 Years in Guizhou Province - WU Chunyan, DENG Yinglan, ZHAO Ping, HU Shixiu, WU Xiaoyan, ZHU Yan, LI Xiangyan, XIE Zhengzhou, WANG Rong, GAO Yan, YANG Xiuying, XU Haina, LU Ran, RAN Limei (Zhongguo quanke yixue, 2024)
Background Urinary incontinence often occurs in women aged 40-60 years and contributes to a significant impact on women's physical health and quality of life. Objective To explore the prevalence and influencing factors of urinary incontinence and its impact on quality of life in women aged 40-60 years in Guizhou Province. Methods From June 2022 to January 2023, women aged 40-60 years who underwent health checkups in 10 hospitals in 7 regions of Guizhou Province were selected as the study subjects. A self-designed general data questionnaire was used to collect the basic data of the study subjects, and International Consultation on Incontinence Questionnaire-Female Lower Urinary Tract Symptoms (ICIQ-FLUTS) and Incontinence Quality of Life Measure (I-QoL) were used to determine the severity of urinary incontinence and the level of quality of life of the study subjects, respectively. Different types of incontinence, including stress incontinence, urge incontinence, and mixed incontinence, were determined according to the diagnostic criteria established by the International Continence Society (ICS). Multivariate Logistic regression analysis was used to explore the influencing factors of urinary incontinence, and explore the effects of different types and severity levels of urinary incontinence on patients' quality of life. Results A total of 3 000 questionnaires were distributed, and 2 966 valid questionnaires were collected, with a valid recovery rate of 98.9%. The prevalence of urinary incontinence among the 2 966 study subjects was 33.4% (991/2 966), including 20.1% (596/2 966) for stress incontinence, 2.0% (58/2 966) for urge incontinence, and 11.4% (337/2 966) for mixed incontinence. Multivariate Logistic regression analysis showed that physical exercise, menstrual status, parity, history of pelvic organ prolapse, perineal laceration, and lateral episiotomy were the influencing factors of stress incontinence (P<0.05) ; history of pelvic surgery, number of miscarriages, and neonatal weight were the influencing factors of urge incontinence (P<0.05), waist circumference, history of chronic pelvic pain, pelvic organ prolapse, perineal laceration were factors associated with mixed incontinence (P<0.05). The total score of I-QoL, scores of behavioral limitations, psychological impact, and social activities impairment were lower in patients with mixed incontinence than those with stress and urge incontinence (P<0.05) ; the total score of I-QoL, scores of behavioral limitations, psychological impact, and social activity impairment were lower in the severe incontinence patients than those with mild and moderate incontinence (P<0.05) . Conclusion Guizhou Province has a higher prevalence of urinary incontinence of 33.41% in women aged 40-60 years, influencing factors differ for different types of urinary incontinence, mixed incontinence and severe urinary incontinence have the greatest impact on patients' quality of life, to provide a reference basis for prevention and health management in this population.